2005
DOI: 10.1021/bm0494242
|View full text |Cite
|
Sign up to set email alerts
|

Production of Starch Foams by Twin-Screw Extrusion:  Effect of Maleated Poly(butylene adipate-co-terephthalate) as a Compatibilizer

Abstract: Free-radical-initiated grafting of maleic anhydride (MA) onto poly(butylene adipate-co-terephthalate) (PBAT), a biodegradable aliphatic-aromatic copolyester, was performed by reactive extrusion. 2,5-Dimethyl-2,5-di(tert-butylperoxy)hexane was used as the free-radical initiator. The peroxide concentration was varied between 0.0 and 0.5 wt % at 3.0 wt % MA concentration; the MA concentration was varied between 1.0 and 5.0 wt % at 0.5 wt % peroxide concentration. The reaction temperature was maintained at 185 deg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
97
2
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 163 publications
(102 citation statements)
references
References 47 publications
1
97
2
2
Order By: Relevance
“…In the study of the maize starch/PBAT foams using maleic anhydride in the maleatation of the polyester, Nabar et al [7] found that this process was efficient in promote a greater interfacial adhesion and no phases separation of the blends were observed. Raquéz et al [19] evaluated the utilization of MA as compatibilizer in starch/ PBAT blends and observed that the presence of MA improved the compatibility between the polymeric phases, provided by the grafting of anhydride in the starch and after promoting acid-catalyzed transesterification reactions.…”
Section: Scanning Electron Microscopy (Sem) Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…In the study of the maize starch/PBAT foams using maleic anhydride in the maleatation of the polyester, Nabar et al [7] found that this process was efficient in promote a greater interfacial adhesion and no phases separation of the blends were observed. Raquéz et al [19] evaluated the utilization of MA as compatibilizer in starch/ PBAT blends and observed that the presence of MA improved the compatibility between the polymeric phases, provided by the grafting of anhydride in the starch and after promoting acid-catalyzed transesterification reactions.…”
Section: Scanning Electron Microscopy (Sem) Analysismentioning
confidence: 99%
“…Native starch is considered a non-plastic material, requiring thermal-mechanical processing, in the presence of plasticizers, with the aim to disrupt their semi-crystalline structure and result in an amorphous material, called thermoplastic starch (TPS) [3,4] . There are several current researches in order to use TPS as a biodegradable packaging material, however, this still have some disadvantages, as the elevated influence of the environmental conditions, defficient mechanical properties and difficulty in their stability and processability [5][6][7] . Among the proposals to improve the starch films properties, the production of blends of starch associated with syntetic polymers, as PBAT (poly (butylene adipate co-terephthalate)) have been broadly studied.…”
Section: Introductionmentioning
confidence: 99%
“…This particular composition has already shown to retain enough melt-strength as well as sufficient grafting extent. [33] These MA-g-PBAT chains were then reactively melt-blended with talc via esterification reactions. Tin(II) octoate (Sn(Oct) 2 ) and 4-dimethylaminopyridine (DMAP) were studied as esterification catalysts.…”
Section: Full Papermentioning
confidence: 99%
“…[25] In practice, the reactive extrusion maleation of PBAT was carried out using 3 wt.-% MA, and 0.5 wt.-% 2,5-dimethyl-2,5-di(tert-butylperoxy) hexane (Luperox 101) as free-radical initiator in order to retain enough melt-strength as well as sufficient percentage grafting for the resulting MA-g-PBAT. [33] The maleation process was carried out at 185 8C, which was a temperature high enough to avoid the homopolymerization of MA. It is worth recalling that the temperature does not significantly affect the grafting percentage of MA onto the polyester backbone.…”
Section: Two-step Reactive Extrusionmentioning
confidence: 99%
“…Because of its interesting thermal and mechanical properties, PBAT, as biodegradable aliphatic-aromatic copolyester, represents a promising candidate in the preparation of starch-based products with useful end applications, while maintaining the biodegradability of the overall composition. 31,32 In contrast to TPS, the low melt-viscosity of MTPS, together with its increased reactivity led, by melt-blending with PBAT, to the formation of stronger covalent bonds at the MTPS-polyester interface, and therefore a finer phase morphology for the resulting melt-blends. 30 However, compared with those of pristine PBAT, it was observed that the occurrence of acid-promoted hydrolysis, inter-and intramolecular transesterification reactions underwent by the polyester matrix.…”
Section: Introductionmentioning
confidence: 99%